FRAUD MITIGATION BY EMBODYING MAQASHID SHARIA VALUES AND ISLAMIC WORK ETHICS - Qorny, Farah Nurani; Laela, Sugiyarti Fatma; Fachrul Avivy, Ahmad Levi (UI Scholars Hub, 2024)
This research examines how the fraud square influences fraud, and investigates whether implementing tahdzib al-fard (educating individuals), part of Maqashid Sharia values, and Islamic Work Ethics (IWE), can reduce employee involvement in fraud. The study uses a quantitative approach with questionnaires for data collection, with 257 civil servants in Banten Province agencies, Indonesia, as study samples. The data were further tested using partial least squares structural equation modeling. The study reveals that pressure, opportunity and rationalization have a positive relationship with fraud, while integrity has no impact on fraud deterrence. Tahdzib al-fard significantly influences employee perceptions and attitudes towards dealing with fraud triggers and increasing integrity. IWE was found to only moderate the relationship between pressure and fraud. The research captures the prevalence of fraud in Banten Province government agencies through the lens of the fraud square. It also proposes a new measurement of tahdzib al-fard, combined with the internalization of IWE, as a promising approach that weakens the drivers of fraud and has implications for reducing the level of fraud in the government sector.